Determination of the Corrosion and Biocompatibility Properties of As-Cast TiNi Alloys - Minja Miličić Lazić; Dijana Mitić; Biljana Dojčinović; Marko Lazić; Aleksandra S. Popović; Branimir N. Grgur (Metals)
In this study, a TiNi alloy with a composition of 50 at.% of titanium and 50 at.% of nickel is investigated in terms of its corrosion and biocompatibility behavior for biomedical applications. The corrosion measurements, which include the determination of open-circuit potential and linear polarization resistance measurements, cyclic polarization measurements, and electrochemical impedance spectroscopy in 9 g L−1 NaCl, show that TiNi has satisfactory corrosion stability. According to the SEM and EDS analysis, after cyclic polarization, pitting corrosion occurred, accompanied by the dissolution of the unstable Ti2Ni inclusions. The analysis also showed that TiNi has good biocompatibility for human osteoblast-like cells, as determined by the mitochondrial activity, which was assessed using a direct contact test following ISO standard 10993-5, via scanning electron microscopy (SEM) and fluorescent microscopy.